Workshop. Diabetes and physical activity in childhood and adolescence - Chiarelli, Francesco; Prisco, Francesco; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2006)
In addition to insulin therapy, diet and education, regular physical activity is usually considered to play a key role in the management of children and adolescents with type 1 diabetes mellitus (T1DM). It improves insulin sensitivity, increases glucose utilization, reduces cardiovascular risk factors, and helps to prevent obesity...